Kako podjetna je Slovenija: Global Entrepreneurship Monitor Slovenija 2002 - Rebernik, Miroslav; Tominc, Polona; Glas, Miroslav; Pšeničny, Viljem (University of Maribor Press, 2003)
Monograph, based on the data of the Global Entrepreneurship Monitor 2002, notes that Slovenian society has not yet functioned as an entrepreneurial society. It has not yet come to realize that for the successful development coordinated cooperation of the state and entrepreneurs is necessary, because no one can force the entrepreneur to grow, recruit and develop. All this can only come from his personal motivation, which depends on the conditions created by the society. Therefore, the fundamental challenge that lies ahead is how to establish a clear vision for long-term development of Slovenia as an entrepreneurial society, and to create a stimulating environment to enable more people embark on entrepreneurship career. Significant changes require more persistence and a long-term effort to operate more efficiently in a number of government departments and in many parts of society that is generate or suppress motivation for entrepreneurial activities. It is important that the government entrepreneurship policy is consistent and therefore predictable for individuals who opt entrepreneurship as their career. This also requires concerted action by the central government and local authorities.